Prealgebra (7th Edition)

Published by Pearson
ISBN 10: 0321955048
ISBN 13: 978-0-32195-504-3

Chapter 4 - Section 4.6 - Complex Fractions and Review of Order of Operations - Exercise Set - Page 285: 56



Work Step by Step

$\frac{1-\frac{x}{4}}{2+\frac{3}{8}}$ $=(1-\frac{x}{4})\div(2+\frac{3}{8})$ $=(1-\frac{x}{4})\div(\frac{16}{8}+\frac{3}{8})$ $=(1-\frac{x}{4})\div\frac{19}{8}$ $=(1-\frac{x}{4})\times\frac{8}{19}$ $=\frac{8}{19}(\frac{1}{1}-\frac{x}{4})$ Use the distributive property to distribute $\frac{8}{19}$ to $(\frac{1}{1}-\frac{x}{4})$ $=\frac{8}{19}-\frac{8x}{76}$ $=\frac{8}{19}-\frac{2x}{19}$ $=-\frac{2x}{19}+\frac{8}{19}$ (generally the $x$ term is written before the term with no variable when expressing simplified polynomials)
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.